Implementation of the Police Goes to School Program by the Education and Training Unit in Reducing Traffic Violations Among High School/Vocational Students - Hayuningtyas, Muthia (Advances in Police Science Research Journal, 2024)
Increased traffic violations committed by high school / vocational students due to lack of socialization about orderly traffic, low student awareness and lack of supervision of traffic rules in Purwakarta Regency. So that the Purwakarta Police Traffic Unit must prioritize education to the community in this case to students by optimizing the Purwakarta Regional Police Unit Special Unit through the Police Goes To School program to students in the hope of overcoming traffic problems in Purwakarta. The purpose of this study is to determine the condition and performance of the Dikyasa Unit, to know the intensity and factors that influence the implementation of the Police Goes To School program in 3 (three) years. The research location is in the Purwakarta Police Precinct. This study uses qualitative methods, Theory of Management and Communication as well as several concepts. The data collection techniques used are interviews, observation, and study of documents. The results obtained in this study are the implementation of the Police Goes To School program in the District Police Council in Purwakarta which has not been carried out properly due to factors that influence such as planning, quality and quantity of personnel, budget, how to deliver material, accommodation and location so that the community security program in the district Purwakarta has not yet been reached. The writer suggests to coordinate and supervise the shortcomings in the Purwakarta Police Dikyasa Unit, improve the quality and quantity of personnel, and the need for innovation in the implementation of the Police Goes To School program so that the goals are conveyed to all students so that the number of traffic violations by students is reduced and the realization kamseltibcarlantas in Purwakarta Regency.